2021
DOI: 10.3390/ijms23010121
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Clock Gene mRNAs and Clock Proteins in Human Psoriatic Skin Samples

Abstract: Psoriasis is a systemic inflammatory skin disorder that can be associated with sleep disturbance and negatively influence the daily rhythm. The link between the pathomechanism of psoriasis and the circadian rhythm has been suggested by several previous studies. However, there are insufficient data on altered clock mechanisms in psoriasis to prove these theories. Therefore, we investigated the expression of the core clock genes in human psoriatic lesional and non-lesional skin and in human adult low calcium tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Clock genes and the cell cycle regulators can in turn affect the up-regulation of their expression and thus participate in abnormal cell proliferation. After Per2 gene knockout, the expression of CLOCK/BMAL1 gene may contribute to the hyperproliferation of psoriasis [30]. The coordination of the cell cycle in epidermal stem cells by core components of the molecular clock indicating that circadian clock might contribute to the hyperproliferation of keratinocytes in the basal layer of psoriatic plaques [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Clock genes and the cell cycle regulators can in turn affect the up-regulation of their expression and thus participate in abnormal cell proliferation. After Per2 gene knockout, the expression of CLOCK/BMAL1 gene may contribute to the hyperproliferation of psoriasis [30]. The coordination of the cell cycle in epidermal stem cells by core components of the molecular clock indicating that circadian clock might contribute to the hyperproliferation of keratinocytes in the basal layer of psoriatic plaques [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…30 , 38 Indeed, recent studies have also linked the circadian clock to psoriasis, sensitive skin and atopic dermatitis. 39–42 Moreover, it was reported that poor sleep quality deregulated the immune system and impaired the integrity of collagen fibers, 43 , 44 which might another reason for the reduction of skin elasticity and firmness. Therefore, we speculated that the significant reduction of skin firmness and elasticity in the late bedtime group was probably also linked with altered circadian rhythms caused by regular late bedtime.…”
Section: Discussionmentioning
confidence: 99%
“…To unravel the link between the circadian clock and psoriasis, a transcriptomic study showed a downregulation of CRY1/2, REVERBA, CLOCK, BMAL1 and RORA/C in keratinocytes from psoriatic lesions ( 269 ). A recent study found changes in core clock genes and clock proteins in non-lesional and lesional human skin samples in psoriasis ( 270 ). In a mouse model, imiquimod-induced psoriasis-like dermatitis was ameliorated in mice with a loss of function mutation in the Clock gene compared to wild-type mice.…”
Section: Epidemiological and Experimental Evidence That Shift Work Co...mentioning
confidence: 99%